EFEKTIVITAS KOMUNIKASI TERAPEUTIK TERHADAP PENINGKATAN PERILAKU HIDUP SEHAT ORANGTUA BALITA DI DEMAK - Widya Ratna Wulan; Evina Widianawati (Dian Nuswantoro Semarang, 2020)
Healthy life behavior is closely related to the stunting impact on toddlers making the government to establish an impact prevention intervention program to toddler’s parents by Posyandu personnel. The intervention by using therapeutic communications are assessed as effective in delivering such information interventions. This study aimed to analyze the effectiveness of therapeutic communication towards healthy life behavior improvement of toddler parents in Demak. Study used descriptive design with a quantitative approach. Study's population were all parents (mother or father) of toddlers in Demak District, Dempet subdistrict, Kedungori village from December 2019 to February 2020, amounting to 78 people. Samples were equal to the number of population taken using the saturated sample technique amounted to 32 respondents. The structured questionnaire instrument is used to obtain the healthy life behaviour change data of the toddler's parents by using therapeutic communication through Pre Test (X) and Post Test (Y) results. The result of using the Wilcoxon Signed Rank Test is known as ? < 0.05, which means there was a difference in the results of Pre Test value with Post Test. So, there is an increase in healthy living behavior towards the toddler's parents by using therapeutic communication